Optimizing Tongue Fluid Sampling and Testing Protocols for Enhanced PRRSV Isolation from Perinatal Swine Mortalities - Onyekachukwu Henry Osemeke; Isadora Machado; Elisa De Conti; Mariah Musskopf; Mafalda Pedro Mil-Homens; Samuel Stutzman; Baoqing Guo; Thomas Petznick; Gustavo De-Sousa-E Silva; Phillip Gauger; Jianqiang Zhang; Daniel C. L. Linhares (Viruses)
Porcine reproductive and respiratory syndrome virus (PRRSV) remains a major concern for swine health. Isolating PRRSV is essential for identifying infectious viruses and for vaccine formulation. This study evaluated the potential of using tongue fluid (TF) from perinatal piglet mortalities for PRRSV isolation. Four collection protocols were tested: extracting TF from fresh tissues using phosphate-buffered saline (PBS group), extracting TF from fresh tissues using virus transportation medium (VTM group), extracting TF from freeze-thawed tissue (freeze-thaw group), and using tissue homogenates (homogenate group). Two cell lines (ZMAC and MARC-145) and primary alveolar macrophages (PAM) were evaluated for their effect on successful PRRSV isolation. An eligible PRRSV-positive unstable breeding herd in Midwestern USA was chosen for the study. Tongues were collected in 20 batches (~30 mortalities per batch). Within each batch, each tongue tissue was cut into four quarters, with each quarter randomly assigned to one of the four collection protocols and RT-qPCR tested. Virus isolation (VI) was attempted on 10 batches. The mean RT-qPCR cycle threshold (Ct) values for the PBS, VTM, freeze-thaw, and homogenate groups were 21.9, 21.8, 22.6, and 24.8, respectively. The VI success rate was 22.6%, 12.1%, 2.8%, and 2.8% in the PBS, VTM, freeze-thaw, and homogenate groups, respectively. The probability of successful VI was 3.1% and 21.0% in the MARC-145 and ZMAC cell lines, respectively, and 4.8% in the PAM cells. TF from perinatal mortalities is an option for PRRS VI, aiding in PRRSV monitoring and control programs.